ANALISIS PESERTA DIDIK BERKEPRIBADIAN INTROVERT KELAS X JURUSAN PEMASARAN SMK NEGERI 3 PONTIANAK - Musrifah, Musrifah; Yuline, Yuline; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIntroverted personality is a personality that has a good understanding of the world in itself. Every student in the Marketing Department is expected to have an ectrovert personality, be open to the people around, but in reality there are still students who are introverted. The purpose of this study is to overview of students with introverted personality in class X MARKETING DEPARTMENT OF PONTIANAK 3 STATE VOCATIONAL SCHOOL. (1) Factors that cause students with introverted personality in class X of the Marketing Department of Public High School 3 Pontianak. (2) Impact that occurs on students who have introverted personality in class X Marketing Department of Vocational High School 3 Pontianak. (3) The Role of Counseling Teachers towards students with introverted personality in Class X of the Marketing Department of Public High School 3 Pontianak. The method used is descriptive method and the form of research is a form of survey research. The subjects this study were three students. His research uses a qualitative approach. Data collection techniques used observation, interviews, and documentation. Based on the results of the research that caused introverted students because of: internal factors and external factors. The impact of introverts is that they have few friends.Â Keywords: Introvert, Learners, Personality